Evaluation of the Management of the Padang City Tourism Office Website in Promoting Tourism in Padang City: Evaluasi Tata Kelola Website Dinas Pariwisata Kota Padang Dalam Promosi Wisata Kota Padang - chessy anha; Rizki Syafril (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to evaluate the governance of the website pariwisata.padang.go.id as a medium for tourism promotion by the Padang City Tourism Office. The background of this study stems from the phenomenon of low utilization of the website by the community and tourists, even though it has been developed as part of the implementation of e-government policies. This study uses a qualitative method with a descriptive approach, as well as the CIPP (Context, Input, Process, Product) evaluation theory proposed by Daniel L. Stufflebeam (1966) as the analytical framework. Data was obtained through in-depth interviews with the Tourism Office, marketing staff, and the public or tourist visitors. The results of the study show that the website was created as a digital promotional tool, but its management is not yet optimal. The main factors that hinder this are the limited number of human resources competent in the field of information technology, the absence of a special team and training, a lack of budget, and a lack of updates and socialization to the public. Therefore, it can be concluded that the website pariwisata.padang.go.id has not functioned optimally as a tourism promotion medium and requires comprehensive improvements in terms of management, content, and publication strategy.